Likely optical counterpart of the cool middle-aged pulsar J1957+5033. Issue 4 (13th May 2022) - Zyuzin, D A; Zharikov, S V; Karpova, A V; Kirichenko, A Yu; Shibanov, Yu A; Geier, S; Potekhin, A Y; Suleimanov, V F; Cabrera-Lavers, A
ABSTRACT: The 840-kyr-old pulsar PSR J1957+5033, detected so far only in γ- and X-rays, is a nearby and rather cool neutron star with a temperature of 0.2–0.3 MK, a distance of 1 kpc, and a small colour reddening excess E ( B − V ) ≈ 0.03. These properties make it an ideal candidate to detect in the optical to get additional constraints on its parameters. We thus performed the first deep optical observations of the pulsar with the 10.4 m Gran Telescopio Canarias in the g ′ band and found its possible counterpart with g ′ = 27.63 ± 0.26. The counterpart candidate position is consistent with the X-ray coordinates of the pulsar within the 0.5 arcsec accuracy. Assuming that this is the real counterpart, we analysed the pulsar X-ray spectrum together with the derived optical flux density. As a result, we found that the thermal emission from the bulk surface of the cooling neutron star can significantly contribute to its optical flux. Our multiwavelength spectral analysis favours the pulsar nature of the detected optical source, since it provides physically adequate parameters of the pulsar emission. We show that the optical data can provide new constraints on the pulsar temperature and distance.